Corrosion resistance evaluation of Ni‐P\nano‐ZrO2 composite coatings by electrochemical impedance spectroscopy and machine vision method. Issue 7 (27th November 2014) - Stankiewicz, A.; Winiarski, J.; Stankiewicz, M.; Szczygieł, I.; Szczygieł, B.
<x xml:space="preserve">Abstract</x> Ni‐P\nano‐ZrO2 composite coatings were obtained on the AISI 304 steel substrate by the electroless method from a bath containing dodecyltrimethylammonium bromide (DTAB). This cationic surfactant prevents ZrO2 agglomeration in the bath and affects the ZrO2 content in the coating, hence it alters functional properties of the coatings. It has been found in this study that corrosion resistance of the composite coatings depends on the surfactant concentration in the bath. The estimation of corrosion resistance was carried out by electrochemical impedance spectroscopy. The degree of the sample surface coverage with corrosion products was determined by the machine vision method. The coating obtained from the 0.88 g/dm3 DTAB solution showed the best protective properties. The machine vision method was shown to be an effective complementary tool to evaluate protective properties of the coatings.